(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
After a small brachiopod fauna was published in 2010 from the Tortonian Sant’Agata Fossili Formation of Tetti Borelli (N Italy), two new and more numerous brachiopod collections turned up from this locality. The Roest Collection in the Naturalis Biodiversity Center (Leiden, the Netherlands), and the Pavia-Giuntelli Collection in the Department of Earth Sciences of Torino University (Torino, Italy) contain 199 and 131 specimens, respectively. Based on the study of these collections, the Tetti Borelli brachiopod fauna is now much better known and more diverse. Additionally to the previously described six species (Cryptopora lovisati, Eucalathis aff. tauriniensis, Megathiris detruncata, Joania aff. falunica, Megerlia truncata, Lacazella mediterranea), another four taxa have been found (Lingula sp., Terebratulina retusa, Joania cordata, Argyrotheca sp.), and a new Megathyrididae genus and species (Borellithyris gaetanii n. gen. n. sp.) has been discovered. Another new species (Eucalathis giulioi n. sp.) is introduced on the basis of a dorsal valve of the Roest Collection and a previously illustrated ventral valve from the Janssen Collection. This is the sixth known fossil Eucalathis species, most of which are described on the basis of a few specimens. The Tetti Borelli brachiopods are mostly resedimented with different degree of transport, but the minute rhynchonellide Cryptopora seems to be more or less autochthonous.